(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article describes a vivid expression of national identity, values, centuries-old traditions and way of life, mental characteristics, national and cultural identity of the Uzbek language in phraseological units. Phraseological units are recognized as a form of folklore, reflecting the national and cultural identity of the language, the structure of everyday consciousness and expressing certain spiritual and cultural meanings.